Avaliação de Objetos de Aprendizagem: cruzando caminhos e produzindo novos olhares - Melo, Janete Aparecida Pereira (2009)
The purpose of this paper is to present the results of a research involving the assessment of the object of learning. For that use the object of learning What is this Galvanization thing? , carried out by the Chemistry team of RIVED, at a public University in the state of Minas Gerais. The investigation approach is qualitative, actually a case study, as this research aims at reaching a deep understanding of one particular case, considering its context and complexity. Coherently to this option, the research techniques used in the data collecting were observation and analysis of documents, questionnaire, interview and field notes, as well as bibliographical research. The theoretical basis for this study is made up mainly by authors who study educational assessment and learning objects. Analysis showed that the teacher holds, as a parameter for object qualification, the appropriateness of the contents and their facility in use, due to the fact that there is a great worry on the fact of not wasting time because of the quantity of issues to be studied during the school term. On the other hand, the specialist focused on the pedagogical matter of the learning objects, claiming that, apart from the technological apparatus, it is necessary to think about the strategies of teaching, the language used and the use of this information. The students eyes were fixed on the ergonomic requisites of the object, due to the fact that their ability to deal with the virtual world has transformed them into excellent observers of these characteristics. The crisscrossing of these different points of view, allows us to say that the quality of an object is involved in its pedagogic adjustment and facility of use. This pedagogic adjustment involves right from the selection of subjects to be studied, to the didactic strategy to be used in the classroom. The facility in use involves the quality of the layout, interactivity and the quality of texts and simulations, as well as the capacity of execution in different platforms and types of machines.